Gestão de unidades de conservação no Brasil: desafios e oportunidades - Silveira, David Aurélio Lima (2025)
Biodiversity conservation and sustainable development are central challenges of environmental management in Brazil, where Protected Areas play a strategic role. The challenges, opportunities, and strategies of Protected Area management in Brazil were analyzed with the aim of identifying pathways to promote biodiversity conservation and sustainable development. This study examined, in an interdisciplinary manner, three main axes: factors compromising management efficiency, the role of public concessions, and the potential of sustainable tourism. The analysis, based on a descriptive methodology, revealed structural barriers such as the scarcity of financial and human resources, institutional fragmentation, and the lack of effective community participation. Concessions were identified as support instruments for management, provided they are aligned with conservation objectives, with state monitoring being essential to prevent conflicts between economic and environmental interests. Sustainable tourism was found to be a practice with the potential to reconcile conservation and local development, provided it is guided by rigorous planning, appropriate regulation, and continuous monitoring. It is concluded that strengthening governance, promoting interinstitutional integration, and engaging local communities are fundamental for Protected Areas to consolidate themselves as spaces that balance environmental protection, socio-environmental justice, and the generation of economic benefits.